Report of the fourteenth session of the Committee for the inland fisheries of Africa (Food and Agriculture Organization of the United Nations Regional office for Africa, 2007)
This document is the report of the fourteenth session of the Committee for Inland Fisheries of Africa (CIFA), which was held in Accra, Ghana, from 22 to 24 November 2006. The major topics discussed were: reports of some intersessional activities; regional dimensions of inland fisheries development; regional dimensions of aquaculture development; role and responsibilities of CIFA; development, use and dissemination of improved seed for aquaculture and proposals for the major topics for discussion at the fifteenth session of CIFA.